Comparative analysis of the Express.js and ElysiaJS frameworks in the context of web application development - Damian Kostrzewa; Marek Miłosz (Journal of Computer Sciences Institute)
JavaScript-based programming frameworks allow more and more web applications to be built, aiming to become the fastest platform for a particular application. The aim of this paper is, among other things, to conduct study to obtain performance results of two server-based programming libraries in the application of an online transaction database structure. The database structure, the TPC-C benchmark queries and the Bombardier HTTP(S) query measurement tool were used to perform the tests. The research thesis "The Express.js framework has better performance than ElysiaJS in terms of TPS measurement tests in TCP-C structure" was set. The results obtained did confirm the thesis.